2016
DOI: 10.1108/ijcst-10-2015-0113
|View full text |Cite
|
Sign up to set email alerts
|

Design preferences on wearable e-nose systems for diabetes

Abstract: Purpose The purpose of this study is to investigate potential users’ preferences and expectations for fabric-based wearable e-nose system designs in order to develop painless and non-invasive monitoring systems for diabetes. Design/methodology/approach After developing a fabric-based wearable sensor, this study used an online survey with a mixture of closed- and open-ended questions about people’s desires and preferences for use-contexts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The majority of IASD (60%) and PASD (83.3%) preferred to receive the monitored data through smartphone apps due to their ease of downloads, ubiquity, and portability, which is the similar to the results of the previous research on WT for healthcare (Koo et al, 2016).…”
Section: 5 Data Notificationsupporting
confidence: 80%
“…The majority of IASD (60%) and PASD (83.3%) preferred to receive the monitored data through smartphone apps due to their ease of downloads, ubiquity, and portability, which is the similar to the results of the previous research on WT for healthcare (Koo et al, 2016).…”
Section: 5 Data Notificationsupporting
confidence: 80%
“…Healthcare-related wearable technology sectors (e.g., medical, fitness, wellness) account for the largest portion of the total growing wearable technology market (Kim & Shin, 2015;Koo et al, 2016). Wearable devices for fitness tracking, frequently used by bike riders, occupy the greatest number of units in worldwide wearable device sales (Gwilt & Rissanen, 2011;Harrop, Hayward, Das, & Holland, 2015;Nusca, 2015).…”
Section: Wearable Technology For Healthcare and The Apparel Industrymentioning
confidence: 99%
“…Females constitute a significant market segment in the wearable technology market that deserves attention: females purchase wearable technology for fitness more often than males (The NPD Group, Inc., 2015). Previous studies illustrate the market potential of wearable technology designed to complement female bike riders' clothing needs and its usefulness by adding innovative clothing functions distinctive from traditional bike wear (Gwilt & Rissanen, 2011;Koo et al, 2016). For example, Gwilt and Rissanen (2011) addressed easy transformability by integrating wearable technology into clothing, allowing females to present themselves in multiple ways by changing design details (e.g., colors, motif, sizes, sleeve lengths) and garment types (e.g., jacket, cape, bag).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, significant differences were found between novice users (NC) and experienced users (EX) in their technology acceptance (Fishbein and Ajzen 1977), decision criteria (Bettman and Sujan 1987), perceived usefulness and periods of use (O'Cass and Fenech 2003;Smith and Brynjolfson 2001), purchase intentions (Sherrell et al 2015), and use motivators (Stragier et al 2016). Although, there is research on understanding user needs and wants for wearables (Gao et al 2015;Koo and Fallon 2017;Koo et al 2016;Stead et al 2004), little attention has been paid to understanding the differences between NC and EX of wearable trackers. In addition, interviews are considered key techniques of user-centered design methodology, but there is a lack of research seeking to hear consumers' actual voices (Holtzblatt et al 2004).…”
mentioning
confidence: 99%